Organisasi Pendidikan Dalam Peningkatan Mutu Pembelajaran di SMAN 103 Jakarta - Fransisca Sophia; Ginola Muhammad Safier; Intan Aulia Rahma (Simpati, 2023)
The study serves three purposes. First, it explains the strategy and the impact the education organization has on the quality of the study at SMAN 103 Jakarta. Second, explain the comparative learning pattern before and when the pandemic. Third, explaining the direction of progress in SMAN 103 Jakarta. Generally, each institution of education has an organization that functions as a service management to the community, especially learners. In the improvement of the learning at sman 103 Djakarta, all teachers, leaders and school committees are united to promote learning that pursues excellence but prioritizes character and morality and that seeks high grades but puts honesty first. The study employs a qualitative approach with case study methods, the research data obtained using interviews, observation and documentation. Next, the data analysis technique used in the study is the presentation of data and the deduction deduction. The data that is presented is the result of direct observation of the school where the writer intended. Therefore, it is clear that there is an improvement in the learning at SMAN 103 Jakarta, which will then serve as a benchmark for all parties to play a role in the education organization to improve the quality of learning.